Keefektifan Layanan Konseling Kelompok untuk Meningkatkan Kepercayaan Diri Siswa Sekolah Menengah Pertama - Imro'atun, Siti; Pravesti, (Jurnal Kajian Bimbingan dan Konseling, 2017)
The purpose of this study is to determine the effectiveness of cognitive behavior therapy counseling group in reducing vocational high school student’s doubts in making career decision. The research design uses pretest-posttest control group design. There are two types of instruments used, that is treatment materials and measuring instruments. The treatment instrument consisted of a manual cognitive behavior group counseling guide for the counselor, while the measuring instrument consist a scale of career decision making that had validity R values above 0.320 and reliability of 0.855 and student’s self-reflection sheets. Data analysis using Two-Independent-Sample Test-Mann-Whitney U. Statistical analysis show that the value of zcount> ztable is -3,315 then H0 is rejected. This is show that cognitive behavioral therapy group counseling is effective to reduce vocational high school student’s doubts in making career decision.